Women's enlightenment and early antenatal care initiation are determining factors for the use of eight or more antenatal visits in Benin: further analysis of the Demographic and Health Survey - Michael Ekholuenetale; Chimezie Igwegbe Nzoputam; Amadou Barrow; Adeyinka Onikan (SpringerOpen, 2020)
Abstract Background Within the continuum of reproductive health care, antenatal care (ANC) provides a platform for vital health care functions, such as disease prevention, health promotion, screening, and diagnosis. It has been widely confirmed that by implementing appropriate evidence-based practices, ANC can save lives. Previous studies investigated the utilization of ANC based on the four visits model. The new guidelines set by the World Health Organization 2016 recommended increasing contacts with health providers from four to eight contacts. The present study aims to determine the frequency, determinants, and socioeconomic inequalities of ANC utilization based on the eight or more contacts in Benin. This will provide information for policy makers to improve ANC utilization. Methods We used a population-based cross-sectional data from Benin Demographic and Health Survey (BDHS)-2017-2018. The outcome variable considered for this study was coverage of ≥ 8 ANC contacts. About 1094 women of reproductive age who became pregnant after the new guideline of ≥ 8 ANC contacts was endorsed were included in this study. The determinants for ≥ 8 ANC contacts were measured using multivariable logistic regression. Concentration (Conc.) Index and Lorenz curves were used to estimate the socioeconomic inequalities of ≥ 8 ANC contacts. The level of significance was set at P < 0.05. Results The coverage of ≥ 8 ANC contacts was 8.0%; 95%CI 6.5%, 9.7%. The results of timing of antenatal care initiation showed that women who had late booking (after 1st trimester) had 97% reduction in ≥ 8 ANC contacts compared with women who initiated ANC contacts within the first trimester (adjusted odds ratio (AOR) = 0.03; 95% CI 0.00, 0.21). In addition, women with medium or high enlightenment were 4.55 and 5.49 as more likely to have ≥ 8 ANC contacts, compared with women having low enlightenment (AOR = 4.55; 95% CI 1.41, 14.69 and AOR = 5.49; 95% CI 1.77, 17.00, respectively). Conc. Index for the household wealth-related factor was 0.33; p < 0.001 for urban women and 0.37; p < 0.001 for the total sample. Similarly, Conc. Index for maternal education was 0.18; p = 0.006 for urban women and 0.21; p < 0.001 for the total sample. Conclusion Secondary analysis of the BDHS showed low coverage of ≥ 8 ANC contacts in Benin. In addition, women's enlightenment, early ANC initiation, and socioeconomic inequalities determined the coverage of ≥ 8 ANC contacts. The findings bring to limelight the need to enhance women's enlightenment through formal education, exposure to mass media, and other channels of behavior change communication. Health care programs which encourage early antenatal care initiation should be designed or strengthened to enhance the coverage of ANC contacts in Benin.